Common Fixed Point Theorems for Multi-Fuzzy Mappings via Weak Contractive Conditions in MR-Metric Spaces - Sudha, A.N. Lakshmi; Singh, Dr. T. Rakesh (International Journal of Aquatic Research and Environmental Studies, 2026)
In this paper, we study common fixed point results for multiple fuzzy mappings in the framework of MR metric spaces. By applying a max-type contractive con-dition, we establish the existence and uniqueness of common fixed points for four and six fuzzy mappings in a complete MR-metric space. Using a cyclic iterative construction together with the Hausdorff MR-metric structure, we prove the con-vergence of the generated sequence and demonstrate that all the mappings admit a unique common fixed point. The proposed results extend and strengthen existing fixed point principles by relaxing contraction assumptions and expanding the the-ory to multi-mapping settings. These findings further advance the development of fixed point theory in generalized metric spaces and provide a broader foundation for applications in fuzzy analysis, optimization, and uncertainty modeling